Implementasi Kurikulum Merdeka pada Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Atas - Parida; Idi, Abdullah; Abdurahmansyah; Harto, Kasinyo; Fauzi, Muhammad (Fakultas Agama Islam Universitas Billfath, 2024)
The transition from the 2013 curriculum to the Merdeka curriculum affects all aspects of learning. Therefore, this research aims to analyze the differences in the implementation of the Merdeka Curriculum in Islamic Religious Education learning at State High School 1 Teluk Gelam and State High School 3 Kayu Agung Ogan Komering Ilir. The method used in this research is a qualitative descriptive method with the data sources being the school principal, deputy principal, Islamic religious education teacher who teaches class XI, and 60 class XI students who were used as key informants through observation, interviews, and documentation. Research findings from observations and interviews with data sources show that the implementation of the Independent Curriculum for Islamic Religious Education subjects at SMA Negeri 1 Teluk Gelam and SMA Negeri 3 Kayu Agung will both start in the 2021-2022 academic year. The difference in implementation is that SMA Negeri 1 Teluk Gelam uses a regular system, and SMA Negeri 3 Kayu Agung uses a block system.